"LINGUO-DIDACTIC FEATURES OF PHRASEOLOGICAL UNITS IN ENGLISH AND UZBEK" (Spectrum Journal of Innovation, Reforms and Development, 2023)
In this article, the interdependence and difference of Uzbek and English phraseological units, their translation forms are studied comparatively.